2015
DOI: 10.1186/s13104-015-1538-5
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian adolescents’ oral health trends since 1986: an epidemiological observational study

Abstract: BackgroundOral health is part of general health, and in adolescence, it represents a good individual health indicator. Three country-based oral health epidemiological studies have been developed in Brazil (1986, 2003 and 2010). The objective of this study was to analyze oral disease trends among Brazilian adolescents and to compare these trends to the World Health Organization’s goals with a focus on public health policies implemented between 1986 and 2010.MethodsThis is an epidemiological observational study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
10
0
3
Order By: Relevance
“…Oral health in adolescence represents a good individual health indicator and it is crucial to understand it at this age in order to subsidize health promotion actions [1]. However, oral health problems are highly prevalent in this population [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral health in adolescence represents a good individual health indicator and it is crucial to understand it at this age in order to subsidize health promotion actions [1]. However, oral health problems are highly prevalent in this population [2].…”
Section: Introductionmentioning
confidence: 99%
“…Several potential risk factors for periodontal disease have been reported in oral health epidemiological surveys, namely being male, of black origin, low socioeconomic status and low educational level, smoking, alcoholism, poor oral hygiene, biological factors, genetic factors, psychosocial conditions such as stress and depression and diabetes [2,3,[11][12][13][14][15][16]. Measures like oral hygiene education, patient empowerment for self-care, dental care and intersectoral and interdisciplinary actions and the establishment of public policies are critical to the prevention and treatment of this disease [1,5,7,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulties in expanding supply in the neediest places can be translated into a lack of change in the health situation and in the quality of life of the elderly, who do not have the time to wait for some change. Considering the trend of tooth loss reduction, [21] the timing of structuring a suitable care network in the dental prosthesis specialty to offer care to these individuals may remain without some effective solution. Priority should also be given to the most vulnerable areas, where basic care needs greater matrix support [17] and reduction in edentulism occurs more slowly [22].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Although some studies showed a significant reduction of the disease, even among adolescents, 6,7 in Brazil, the last national survey showed that caries index continued to be high in this age group. 8,9 In addition, the rate of caries lesions progression was reported as higher at adolescents, when compared to young adults participants. 10 It is also worth noting that dental caries in advanced stages can have a negative impact on the quality of life, due to pain, discomfort and infection.…”
Section: Introductionmentioning
confidence: 99%